Studi Kualitatif Pengalaman Remaja Putri yang Mengalami Gangguan Menstruasi di SMP Negeri 2 Bunta Kabupaten Banggai Propinsi Sulawesi Tengah - Mariyati Mariyati; Arlin Adam; Andi Alim (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Adolescence is a critical phase in individual development, especially for adolescent girls who begin to experience menstruation as a sign of reproductive maturity. However, not all adolescents experience menstruation normally; some experience disorders such as menstrual pain, irregular cycles, and prolonged bleeding. This study aims to explore in depth the subjective experiences of adolescent girls with menstrual disorders at SMP Negeri 2 Bunta, Banggai Regency, focusing on the nature of the disorders experienced, their interpretation of these experiences, coping strategies, and the social support received. This study employs a qualitative approach with a phenomenological design. The primary informants were female adolescents in grades VII–IX who had experienced menstrual disorders in the past six months, selected purposively until data saturation was achieved. Data collection techniques included in-depth interviews, non-participatory observation, and document analysis. Data were analyzed using the Miles and Huberman model through data reduction, data presentation, and drawing conclusions. The results of the study indicate that menstrual disorders are viewed as normal by most informants, despite causing physical discomfort and psychological anxiety. Adolescents' responses to these disorders vary, ranging from the use of warm compresses and medication to no intervention at all. The primary sources of information are mothers and social media, while the roles of teachers and schools remain limited. Social support is most commonly provided by family, although some adolescents also feel supported by peers and teachers. This study emphasizes the importance of systematic reproductive health education, school involvement in supporting adolescents, and the creation of safe and stigma-free discussion spaces regarding menstruation-related issues.